Cactus Moth, Cactoblastis cactorum (Berg) (Insecta: Lepidoptera: Pyralidae) - Dale H. Habeck; F. D. Bennett; Christine Miller (EDIS, 2012)
Since its arrival in the Florida Keys in 1989, this invasive species has become a serious threat to the diversity and abundance of Opuntia cactus in North America. The spread of this moth raises concerns about harm to rare opuntioid species (prickly pear and related cacti), the endangerment of wild opuntioids in the southwestern United States and Mexico, and the consequent effects on entire desert ecosystems and economic hardship for communities in Mexico that cultivate and sell Opuntia. This revised 5-page fact sheet was written by D. H. Habeck, F. D. Bennett, and Christine Miller, and published by the UF Department of Entomology and Nematology, September 2012.